Health systems research in a low income country - easier said than done - English, Mike (2008)
Small hospitals sit at the apex of the pyramid of primary care in many low-income country health systems. If the Millennium Development Goal for child survival is to be achieved hospital care for severely ill, referred children will need to be improved considerably in parallel with primary care in many countries. Yet we know little about how to achieve this. We describe the evolution and final design of an intervention study attempting to improve hospital care for children in Kenyan district hospitals. We believe our experience illustrates many of the difficulties involved in reconciling epidemiological rigour and feasibility in studies at a health system rather than an individual level and the importance of the depth and breadth of analysis when trying to provide a plausible answer to the question - does it work? While there are increasing calls for more health systems research in low-income countries the importance of strong, broadly-based local partnerships and long term commitment even to initiate projects are not always appreciated.